Wet Chemical Processing of Ge in Acidic H2O2 Solution: Nanoscale Etching and Surface Chemistry. (16th September 2020) - Abrenica, Graniel Harne A.; Fingerle, Mathias; Lebedev, Mikhail V.; Arnauts, Sophia; Mayer, Thomas; Holsteyns, Frank; de Gendt, Stefan; van Dorp, Dennis H.
Abstract : Herein, we investigate wet-chemical etching of Ge (100) in acidic H2 O2 solutions for technologically advanced device processing. Nanoscale etching kinetics data were provided by inductively coupled plasma mass spectrometry (ICP-MS) measurements. Rotation rate- dependent measurement showed that the hydrodynamics of the system is important. The dependence of the etch rate on the HCl concentration was considered for the range 0.001–1 M HCl. A stark difference morphologically for >1 M HCl, which resulted in a rough surface confirmed by atomic force microscopy (AFM) images, has been observed. X-ray photoelectron spectroscopy (XPS) measurements provided insight in the surface chemistry of etching for device processing. Electrochemical measurements confirmed that the etching process follows a chemical mechanism. Based on X-ray photoelectron spectroscopy (XPS) data, we present reaction schemes that help to understand the results.